Offshoring as a Threat to the National Economic Security: Causes and Ways to Counteract - Volodymyr Hobela; Stepan Melnyk (Науковий вісник Мукачівського державного університету. Серія Економіка, 2021)
The volume of capital outflows from Ukraine to offshore jurisdictions has become quite large and poses a threat to the economic security of the state, however, measures to de-offshorise the economy are not effective. Therefore, this study is aimed at identifying factors that affect the level of offshoring of the economy, in addition to the state's tax policy, and at developing measures to de-offshorise the state economy. The study used general and special methods of cognition, economic, mathematical, and statistical analysis, the method of deduction and theoretical generalisation. A theoretical analysis of offshoring as an economic category is carried out, the scale of offshoring of the world economy and its impact on the economic security of the state is determined, which substantiated the relevance of the chosen research topic. The main factors influencing the level of offshoring of the economy, except for tax evasion, are highlighted. A methodology and algorithm for determining the total amount of capital outflow are proposed and calculations of the total amount of capital outflow from Ukraine for 2013-2019 are carried out. A correlation analysis was carried out to determine the level of influence of certain factors on the offshoring level of the Ukrainian economy. A mathematical model of the influence of these factors is constructed (x1, x2 ... xn) at the level of offshoring of the economy (y), which allowed identifying the factors that most contribute to the increase in the volume of capital outflows from Ukraine. A comparison of the level of corporate raiding, the coefficient of offshoring and the volume of capital outflow from Ukraine is carried out, and a conclusion is made about their stable interdependence. Based on the results of the study, the main ways of de-offshoring of the Ukrainian economy in the process of creating and forming the Bureau of Economic Security of Ukraine are developed. It is proposed to create a division within the specified bureau that will perform the functions of countering raiding and violation of property rights of business entities. It is assumed that these measures would contribute to the de-offshoring of the economy and ensure the economic security of the state. The findings of the study can be used to form legislative and institutional support for de-offshoring and ensure the economic security of the state. In particular, based on the results, it is recommended to form the main directions of work and functions of the newly created Bureau of Economic Security of Ukraine